Rewrite the equation as <math><mstyle displaystyle="true"><mn>5</mn><mi>x</mi><mo>-</mo><mn>4</mn><mrow><mo>(</mo><mi>x</mi><mo>+</mo><mn>7</mn><mo>)</mo></mrow><mo>=</mo><mn>22</mn></mstyle></math> .

Simplify each term.

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>4</mn><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>5</mn><mi>x</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>28</mn></mstyle></math> to both sides of the equation.

Add <math><mstyle displaystyle="true"><mn>22</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>28</mn></mstyle></math> .

Do you know how to Solve for x 22=5x-4(x+7)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.